Comparison of the Saline Infusion Test and the Fludrocortisone Suppression Test for the Diagnosis of Primary Aldosteronism - Willenberg, H. S.; Vonend, O.; Schott, M.; Gao, X.; Blondin, D.; Saleh, A.; Rump, L. C.; Scherbaum, W. A. (Hormone and Metabolic Research, 2012)
For the diagnosis of primary aldosteronism (PA), confirmatory testing is mandatory and different function tests can be employed. There are, however, sparse data comparing the fludrocortisone suppression test (FST) and the saline infusion test (SIT). Patients with PA (n=90) or essential hypertension (n=65) were studied. They underwent one or the other test or both of them. Using the DPC Siemens aldosterone radioimmunoassay, we found that the SIT led to a stronger suppression of aldosterone than the FST. Post-test aldosterone-to-renin ratios (ARRs) and the percentage of suppression of aldosterone serum concentrations performed worse. The same results were observed in patients who underwent both FST and SIT. Some patients had divergent results in both tests. For the SIT, a lower cutoff value should be used than for the FST for the adequate identification of patients with unilateral PA. Long-term prospective studies are needed to address the question at what cutoff values patients benefit from subtype differentiation of PA. We discuss here possible explanations for divergent results obtained with both tests.
Keywords: aldosterone; adrenal; fludrocortisones; hypertension